BEATS: Practical Audit Trail in Blockchain Systems - Bilal Alagha; Ilker Ozcelik (IEEE Access, 2025)
An audit trail records activities and tracks changes within a system, serving as a crucial tool for fraud prevention and data management. However, traditional audit trail systems often face inefficiencies, high costs, and vulnerability to security breaches and unauthorized access, limiting their real-time fraud detection capabilities. These limitations highlight the need for more reliable, secure, and efficient solutions. Blockchain technology, with its decentralized and immutable ledger, provides a promising solution. By providing tamper-proof, transparent, and real-time transaction records, blockchain enhances the reliability, efficiency, and security of audit trails, transforming auditing practices and boosting stakeholder trust. Despite these advantages, a significant challenge remains: as transaction volumes grow, retrieving and verifying specific information becomes increasingly time-consuming and resource-intensive. This problem, often overlooked in research, restricts the scalability and practicality of blockchain-based audit systems. To address these limitations, this study proposes BEATS (Blockchain-based Efficient Audit Trail System) - an efficient approach for verifying specific information within a blockchain. BEATS leverages a Cryptographic Accumulator, a compact data structure that accumulates transaction hashes, enabling auditors to verify transaction authenticity without exhaustive searches or supplementary systems. Our evaluation on the Sawtooth platform compared BEATS against linear transaction search, database-supported search, and platform-specific solutions. Results demonstrate that the RSA-based Cryptographic Accumulator significantly improves verification efficiency, achieving O(1) time and space complexity. This research shows that BEATS enhances the practicality and scalability of blockchain-based audit trail systems for large-scale applications, advancing blockchain technology adoption in domains that demand secure, efficient, and scalable audit solutions.